Association of BMAL1 clock gene polymorphisms with fasting glucose in children: clinical research article - Yang, Yide; Zeng, Yuan; Li, Jian; Zhou, Jun-Hua; He, Quan-Yuan; Zheng, Chan-Juan; Reichetzeder, Christoph; Krämer, Bernhard; Hocher, Berthold (Pediatric research, 2023)
The brain and muscle Arnt-like protein-1 (BMAL1) gene is an important circadian clock gene and previous studies have found that certain polymorphisms are associated with type 2 diabetes in adults. However, it remains unknown if such polymorphisms can affect fasting glucose in children and if other factors modify the associations.